2020
DOI: 10.1002/jcsm.12634
|View full text |Cite
|
Sign up to set email alerts
|

Blended home‐based exercise and dietary protein in community‐dwelling older adults: a cluster randomized controlled trial

Abstract: Background Effective and sustainable interventions are needed to counteract the decline in physical function and sarcopenia in the growing aging population. The aim of this study was to determine the 6 and 12 month effectiveness of blended (e-health + coaching) home-based exercise and a dietary protein intervention on physical performance in community-dwelling older adults. Methods This cluster randomized controlled trial allocated 45 clusters of older adults already engaged in a weekly community-based exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…We selected articles investigating nutrition interventions, macronutrient intake below recommended, and micronutrient deficiency. We found 26 articles: 10 clinical trials, 3,25–33 five cross‐sectional studies, 34–38 three experimental animal studies 39–41 (one of which also included a human cross‐sectional analysis 38 ), three narrative reviews, 6,42,43 two retrospective studies, 44,45 two systematic reviews or meta‐analyses, 46,47 and one questionnaire survey 48 . Within the 320 original and review articles published in 2018, 2019, and 2020 in JCSM , the 26 articles on nutrition that we found comprise approximately 8%.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 92%
See 1 more Smart Citation
“…We selected articles investigating nutrition interventions, macronutrient intake below recommended, and micronutrient deficiency. We found 26 articles: 10 clinical trials, 3,25–33 five cross‐sectional studies, 34–38 three experimental animal studies 39–41 (one of which also included a human cross‐sectional analysis 38 ), three narrative reviews, 6,42,43 two retrospective studies, 44,45 two systematic reviews or meta‐analyses, 46,47 and one questionnaire survey 48 . Within the 320 original and review articles published in 2018, 2019, and 2020 in JCSM , the 26 articles on nutrition that we found comprise approximately 8%.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 92%
“…Of the nutrition studies that we found, one explored the role of protein, 31 three explored the role of vitamin D, 26,38,39 two explored the role of several nutrients, 3,41 and one explored the role of natural product (astaxanthin) supplements 40 . Seven studies 25,27–30,32,33 investigated the effects of multimodal interventions (defined as two or more approaches) on muscle mass. Articles also explored the associations of protein intake, 46,47 iron deficiency, 37,42 micronutrients, 35 calorie restriction, 43 nitrate dietary intake, 36 retrospective evaluation of early dietary supplementation, 44 and overall dietary intake and patterns 34 with several clinical outcomes and/or biomarkers of sarcopenia or cachexia.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 99%
“…The use of blended care, the combination of face-to-face counseling with health technology, is more and more used ( 108 , 109 ). These blended interventions are more effective than “stand-alone” interventions without professional guidance ( 110 ). The integration of online and offline leads to improved adherence rates which is crucial for the effectiveness of digital health technologies ( 82 ).…”
Section: Innovative Strategiesmentioning
confidence: 99%
“…One good example of a blended care intervention for older adults, that was built on well-described theoretical principles of behavior change is the VITAMIN trial ( 111 ). This trial was developed to counteract the decline in physical functioning and sarcopenia using a blended-care home-based exercise and dietary protein intervention and showed positive effects on among others muscle mass, muscle strength and protein intake, but not on physical performance in healthy older adults (55 years and over) ( 110 , 112 ). However, whether this approach also works for frail older people and people with or at risk for sarcopenic obesity should be further explored.…”
Section: Innovative Strategiesmentioning
confidence: 99%
“…It is well established that progressive resistance training combined with strength and balance exercises are safe and effective for improving muscle mass, hip and lumbar spine bone mineral density, and muscle strength and function [ 1 ] and for reducing the risk of falls [ 2 ], hospitalizations, fractures [ 3 ], and mortality. Furthermore, diet has a fundamental role in the health of older adults [ 4 ], and meta-analyses have found that nutritional interventions in addition to physical activity lead to greater improvements in physical function, body composition, and strength in frail and pre-frail older adults [ 5 - 7 ].…”
Section: Introductionmentioning
confidence: 99%